2021
DOI: 10.1016/j.celrep.2021.109798
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced eosinophil-mediated inflammation associated with antibody and complement-dependent pneumonic insults in critical COVID-19

Abstract: Despite the worldwide effect of the Coronavirus disease 2019 (COVID-19) pandemic, the underlying mechanisms of fatal viral pneumonia remain elusive. Here, we show that critical COVID-19 is associated with enhanced eosinophil-mediated inflammation when compared to non-critical cases. In addition, we confirm increased Th2-biased adaptive immune responses, accompanying overt complement activation, in the critical group. Moreover, enhanced antibody responses and complement activation is associated with disease pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 44 publications
1
33
0
1
Order By: Relevance
“…Two studies showed activation of the lectin pathway in the lungs [ 56 , 57 ], however depositions of the lectin pathway were hardly detectable in another study [ 45 ]. In parenchyma of lung tissues of critically ill patients, increased T helper (Th)2-biased adaptive immune response was observed with apparent activation of the complement system (C3b and C5b-9) [ 58 ]. In the kidneys, cleavage products of C3 were heavily present in renal and glomerular arteries.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies showed activation of the lectin pathway in the lungs [ 56 , 57 ], however depositions of the lectin pathway were hardly detectable in another study [ 45 ]. In parenchyma of lung tissues of critically ill patients, increased T helper (Th)2-biased adaptive immune response was observed with apparent activation of the complement system (C3b and C5b-9) [ 58 ]. In the kidneys, cleavage products of C3 were heavily present in renal and glomerular arteries.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this B-cell subset presented the highest enriched gene set scores for phagocytic activity, complement activation, and immune complex response when compared to the other B-cell subsets ( Supplementary Figure 10 ). These enhanced scores suggest a potential contribution in pathogenic humoral responses observed in severe COVID-19 during early stages ( Kim et al., 2021 ). While we could not define whether the differentiation pathway of PC2 cells is linked to an EF B-cell response pathway (AN → DN → AM2), it is plausible that both the AM2 and PC2 cells seem to function as pathogenic B cells.…”
Section: Discussionmentioning
confidence: 94%
“…The presence of substantial evidence has supported the notion that aberrant immune responses to human coronaviruses are typified by the dysregulation of the innate response, including type I and III interferons, alongside an aberrant adaptive immune response against the invading pathogen ( Wong and Perlman, 2022 ). Recently, our group reported that enhanced eosinophil-mediated inflammation and subsequent pulmonary pathogenesis via enhanced T H 2-biased immune responses have been associated with increased formation of immune complexes, and membrane attack complexes in airways and vasculature of inflamed lungs, especially in critical COVID-19 ( Kim et al., 2021 ). In addition, previous seminal studies have reported the potential pathogenic role of dysregulated humoral immune responses, including overt EF B-cell activation ( Woodruff et al., 2020 ) and autoantibodies ( Bastard et al., 2020 ; Wang et al., 2021 ), correlated with severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that FcγRIIA-mediated activation of platelets is linked to thrombocytopenia in critically ill patients [ 45 , 46 ]. Another study reported that enhanced eosinophil-mediated inflammation in the respiratory tract of critically ill and deceased COVID-19 patients is associated with FcγR signaling in myeloid cells [ 47 ]. Finally, neutrophil activation by immune complexes via FcγRIIA was suggested to negatively impact COVID-19 progression [ 48 ].…”
Section: Ic-mediated Immune Cell Activation and Systemic Inflammation...mentioning
confidence: 99%